Sensory Analysis of Sweet Musts in Pedro Ximenez cv. Grapes Dried using Different Methods - Serratosa, M.P.; Marquez, A.; Lopez-Toledano, A.; Merida, J. (South African Journal of Enology and Viticulture, 2016)
The sensory properties of musts from Pedro Ximenez grapes chamber-dried at 40 or 50°C, with or without a dipping treatment, are compared to musts from grapes subjected to the traditional sun-drying method used in the production of sweet wines. The chamber-dried procedure, specifically at 50°C, decreased the drying time, improved the health status of the grapes relative to the growth of fungi that produce toxins and yielded must with a very similar color to that of sun-dried grapes. Sensory evaluation has shown that must from grapes dried at 50°C, after treatment with an alkaline emulsion of ethyl oleate, is unacceptable due to the light color. The musts receiving the highest scores for color, aroma and flavor were from untreated grapes dried at 50ºC or potassium carbonate-treated grapes dried at the same temperature. However, the treatment did not significantly accelerate drying.